Management of bacterial leaf blight of mango through antibiotics and bio-fungicide - Basak, R. P.; Hossain, Ismail; Kashem, M. A.; Mondal, Mohd Monjurul Alam; Yusop, Mohd Rafii (Gaurav Society of Agricultural Research Information Centre, 2014)
An experiment was conducted in the net house, Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh, Bangladesh during 15 July 2012 to June 2013 to find out the efficacy of antibiotics and biofungicide for controlling bacterial leaf blight of mango. Six treatments were applied viz., (i) T1–Gentamycin @ 0.05%, (ii) T2– Erithromycin @ 0.05%, (iii) T3–Doxycycline @ 0.05%, (iv) T4–Copper sulphate @ 0.05%, (v) T5–BAU-biofungicide @ 2% and (vi) T6–Control. The treatment BAU-biofungicide was found good in controlling bacterial leaf blight of mango. This treatment increased 23.71% plant height, 53.33% branch over control and reduced 39.31% disease incidence and 48.50% disease severity when applied as foliar spray @ 2%. The second best control measure was found by gentamycin as it reduced 28.46% disease incidence and 46.43% disease severity when applied as foliar spray @ 0.05%, although other treatments reduced incidence and severity of bacterial leaf blight which were applied as foliar spray @ 0.05%.